Dietary Fiber Intake Is Related to Skeletal Muscle Mass, Body Fat Mass, and Muscle-to-Fat Ratio Among People With Type 2 Diabetes: A Cross-Sectional Study - Fuyuko Takahashi; Yoshitaka Hashimoto; Ayumi Kaji; Ryosuke Sakai; Yuka Kawate; Takuro Okamura; Hiroshi Okada; Noriyuki Kitagawa; Noriyuki Kitagawa; Naoko Nakanishi; Saori Majima; Takafumi Osaka; et al. (Frontiers in Nutrition, 2022)
ObjectivesTo investigate the relationship between dietary fiber intake and skeletal muscle mass, body fat mass, and muscle-to-fat ratio (MFR) among men and women with type 2 diabetes (T2D).MethodsThis cross-sectional study involved 260 men and 200 women with T2D. Percent skeletal muscle mass (%) or percent body fat mass (%) was calculated as (appendicular muscle mass [kg] or body fat mass [kg]/body weight [kg]) × 100. MFR was calculated as appendicular muscle mass divided by body fat mass. Information about dietary fiber intake (g/day) was obtained from a brief-type self-administered diet history questionnaire.ResultsDietary fiber intake was correlated with percent body fat mass (r = –0.163, p = 0.021), percent skeletal muscle mass (r = 0.176, p = 0.013), and MFR (r = 0.157, p = 0.026) in women. However, dietary fiber intake was not correlated with percent body fat mass (r = –0.100, p = 0.108), percent skeletal muscle mass (r = 0.055, p = 0.376), and MFR (r = 0.065, p = 0.295) in men. After adjusting for covariates, dietary fiber intake was correlated with percent body fat mass (β = 0.229, p = 0.009), percent skeletal muscle mass (β = 0.364, p < 0.001), and MFR (β = 0.245, p = 0.006) in women. Further, dietary fiber intake was related to percent skeletal muscle mass (β = 0.221, p = 0.008) and tended to be correlated with percent body fat mass (β = 0.148, p = 0.071) in men.ConclusionDietary fiber intake was correlated with skeletal muscle mass, body fat mass, and MFR among women with T2D.